Programme management in construction - Barnes, Peter, 1954-; Farren, Roy; Haidar, Ali D.; Wells, Kenneth P. (ICE Publishing is a division of Thomas Telford Ltd, a wholly-owned subsidiary of the Institution of Civil Engineers (ICE), 2015)
'Programme Management in Construction' provides a comprehensive introduction to the application of programme management in the construction industry, demonstrating detailed coverage of programme management techniques through best practice guidance and case study examples.